Analisis Pengaturan Hukum Terhadap Kejahatan Siber Doxing Di Indonesia - Prisdallini, Diaz Marsillo; Irawan, Andrie (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Abstract The idea of conducting research related to "Reconstruction of Doxing Cybercrime Regulation in Indonesia", is based on the purpose of knowing; first, what is the background for the emergence of cybercrime, especially doxing cybercrime in Indonesia?; second, to what extent do state institutions in charge of legislative affairs respond to problems (social and legal) due to the development of cybercrime doxing in Indonesia, so that law enforcement officials can anticipate and overcome them?; Third, how can the regulation of cybercrime doxing in Indonesia be reconstructed, so that it can be a solution to the problems that occur? The research method used is a normative juridical method with a legislative approach, a conceptual approach, and a case approach. The results of the study show that: (1) The reality of cybercrime must be observed first from the parent of cybercrime, namely; Cyberspace which is a new reality in human life, identification begins with; (a) analysis of the occurrence of social change as an impact of the development of technological innovation, (b) innovation is an alternative approach for humans as social creatures in interacting, (c) this social interaction forms a newcommunity in the form of a virtual form, namely cybercommunity (cybercommunity/cybersociety), (d) currently a new form of cybercrime has emerged called doxing, which is a violation of the right to personal data. (2) Regulatory readiness in anticipating and overcoming cybercrime, especially doxing cybercrime in Indonesia, begins with; (a) analysis of general regulations on cybercrime, (b) analysis of special regulations on cybercrime, and (c) analysis of problems in cybercrime regulations, especially doxing cybercrime. As a complement to the results of this study, it is recommended to state administrators to respond to the development of cybercrime doxing by reconstructing the current laws and regulations. Keywords: Regulation, Crime, Cyber Doxing Abstrak Gagasan melakukan penelitian terkait “Rekonstruksi Pengaturan Kejahatan Siber Doxing di Indonesia”, didasarkan kepada tujuan untuk mengetahui; pertama, apa yang melatarbelakangi timbulnya kejahatan siber, khususnya kejahatan siber doxing di Indonesia?; kedua, sejauhmana lembaga negara yang membidangi urusan legislasi menyikapi problematika (sosial maupun hukum) akibat berkembangnya kejahatan siber doxing di Indonesia, sehingga aparat penegak hukum dapat mengantisipasi dan mengatasinya?; ketiga, bagaimana sejatinya pengaturan kejahatan siber doxing di Indonesia direkonstruksi, sehingga dapat menjadi solusi atas permasalahan yang terjadi? Metode penelitian yang digunakan adalah metode yuridis normatif dengan pendekatan perundang-undangan, pendekatan konseptual, pendekatan kasus. Hasil dari penelitian memperlihatkan, bahwa: (1) Realita kejahatan siber (cybercrime) harus dicermati terlebih dahulu dari induk kejahatan siber, yaitu; ruang maya (cyberspace) yang merupakan realita baru dalam kehidupan manusia, identifikasi diawali dengan; (a) analisis terjadinya perubahan sosial sebagai dampak dari perkembangan inovasi teknologi, (b) inovasi menjadi pendekatan alternatif bagi manusia sebagai mahkluk sosial dalam berinteraksi, (c) interaksi sosial ini membentuk suatu komunitas baru yang berwujud virtual, yaitu masyarakat siber (cybercommunity/ cybersociety), (d) saat ini muncul bentuk kejahatan siber baru yang disebut doxing, yaitu pelanggaran hak atas data pribadi. (2) Kesiapan regulasi dalam mengantisipasi dan mengatasi kejahatan siber khususnya kejahatan siber doxing di Indonesia, diawali dengan; (a) analisis regulasi umum atas tindak kejahatan siber, (b) analisis regulasi khusus atas tindak kejahatan siber, dan (c) analisis problematika regulasi kejahatan siber khususnya kejahatan siber doxing. Sebagai pelengkap dari hasil penelitian ini, maka direkomendasikan kepada penyelenggara negara agar memberi respon atas berkembangnya kejahatan siber doxing dengan melakukan rekonstruksi peraturan perundang-undangan yang ada saat ini. Kata Kunci: Pengaturan, Kejahatan, Siber Doxing